Developing a method for prediction of relapsing myocardial infarction based on interpolation diagnostic polynomial - Yakubovska, Sofia; Vуsotska Olena; Porvan, Andrei; Yelchaninov, Dmytro; Linnyk, Elena (Eastern-European Journal of Enterprise Technologies, 2016)
In this paper, based on the estimations of expert opinions of the persons who make decisions, we determined a set of criteria for evaluation of the states of patients and of the classes of possible states for predicting the relapsing myocardial infarction. We propose a method for predicting the relapsing myocardial infarction on the basis of the designed interpolation diagnostic polynomial to determine the probability of occurence of the relapsing myocardial infarction. The developed method is based on the methodology of verbal decision analysis. This method makes it possible, taking into account the totality of attributes of disease, their combination and mutual effect, to increase the accuracy of prediction by 2,7 % (in comparison to the method-prototype). This provides a possibility to prevent the relapse of disease and sudden coronary death. The proposed method is of practical interest and may be applied for the diagnosis and prediction of development of other human cardiovascular system diseases.